PENGEMBANGAN PENUNTUN PRAKTIKUM ZOOLOGI VERTEBRATA BERBASIS MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KEMAMPUAN BERFIKIR KRITIS MAHASISWA - Humardani Syam Pratomo, Ryan; Mukminati Nur, Sri (Jurnal Biogenerasi, 2024)
The aim of this research is to develop a Vertebrate Zoology practicum guide based on the Jigsaw learning model,Apart from that, to analyze the feasibility and characteristics of the practicum guide being developed. In the process of developing products, researchers adopt the development and research model of Borg and Gall. The research procedure starts from the preliminary study stage to the field trial stage. Based on the results of 2 validators who assessed the practicum guides that the researchers developed, they produced an average score of 4.82 and 4.59 which were in the very good category. Researchers implemented limited trials on 10 students who had different criteria (high, medium and low ability). Based on limited trials, it was found that the average percentage of results sequentially included 83% (high ability) and 80% (medium and low ability). The application of field trials using the one group pre-test post-test design was used for 1 class. By using SPSS 23 for Windows, the researcher analyzed the data using the one-sample T-Paired test formula. A significance value of 0.000 was obtained through the results of field trial analysis, which means it is lower than 0.05. Based on these results, it can be concluded that there is a significant difference between students' pre-test and post-test scores. So the research results show that the practicum guide that the researchers developed is suitable for application in learning.